2007
DOI: 10.1083/jcb.200612053
|View full text |Cite
|
Sign up to set email alerts
|

RhoG regulates endothelial apical cup assembly downstream from ICAM1 engagement and is involved in leukocyte trans-endothelial migration

Abstract: During trans-endothelial migration (TEM), leukocytes use adhesion receptors such as intercellular adhesion molecule-1 (ICAM1) to adhere to the endothelium. In response to this interaction, the endothelium throws up dynamic membrane protrusions, forming a cup that partially surrounds the adherent leukocyte. Little is known about the signaling pathways that regulate cup formation. In this study, we show that RhoG is activated downstream from ICAM1 engagement. This activation requires the intracellular domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
202
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(221 citation statements)
references
References 31 publications
16
202
2
1
Order By: Relevance
“…transmigratory cups, apical cups, dome structures, ICAM-1-enriched contact areas, or actin dynamic structures. 14,[67][68][69][70][71] The names were based on the hypothesized function or morphology of these structures. Work of Carman and coworkers showed that these structures, that formed both during para-and transcellular diapedesis (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…transmigratory cups, apical cups, dome structures, ICAM-1-enriched contact areas, or actin dynamic structures. 14,[67][68][69][70][71] The names were based on the hypothesized function or morphology of these structures. Work of Carman and coworkers showed that these structures, that formed both during para-and transcellular diapedesis (Fig.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
“…75,76 It has been shown that assembly of F-actin, the major component and driving force to induce such apical protrusions, requires the activation small GTPases RhoG and Rac1. 67,77 Currently, the major function of the docking structure is thought to provide guidance for transmigrating leukocytes. 78 The regulation of the endothelial F-actin cytoskeleton Regulation of leukocyte TEM and vascular integrity both depend on the ability to dynamically remodel the F-actin cytoskeleton in ECs.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%
“…It has been established that cross linking of ICAM-1 or VCAM-1 results in activation of Rac1 (17,32). Moreover, ICAM-1 or VCAM-1 clustering is essential in the formation of docking structures, required for proper leukocyte transendothelial migration, for which Rac1 is the molecular engine (14,16).…”
Section: -Mp/6-t-gtp Inhibit Icam-1 Mediated Docking Structure Formamentioning
confidence: 99%
“…ICAM-1 mAb (R&D Systems) to create ICAM-1-Ab-coated beads to induce docking structure formation on endothelial cells (17).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation